Pertanggungjawaban dan Penegakan Hukum Pidana Korporasi dalam Tindak Pidana Korupsi di Indonesia - Faturachman, Fauzan Azima; Hutasoit, Tomi J.E; Hosnah, Asmak Ul (AKADEMIK: Jurnal Mahasiswa Humanis, 2024)
The times and business complexity have encouraged the important role of corporations in various aspects of life. On the other hand, corporations also have the potential to violate the law, including corruption. Corruption is a complex issue that has a major impact on the environment, economy and community welfare. In some cases, corruption offenses are committed by corporations, so questions arise about corporate criminal liability and law enforcement. Corporate criminal liability is a relatively new concept in Indonesia. This concept allows corporations to be convicted for criminal offenses committed by the management, directors, or employees of the corporation. Based on this relatively new concept, the regulation of corporate criminal liability and law enforcement still raises questions and legal uncertainty.